ePortfolio use by university students in Australia : informing excellence in policy and practice : supplementary report. - Hallam, Gillian; Harper, Wendy; Hauville, Kim; Creagh, Tracy; McAllister, Lynn (Australian Learning and Teaching Council (ALTC), 2010)
This report presents the findings of the AeP project survey (AeP PS). Current and emerging e-portfolio practice in post compulsory education is described, and the e-portfolio scene in late 2010 and late 2007 are compared. The critical success factors for e-portfolio use were widely acknowledged to relate to funding and staffing, as well as the need for adequate support for students in areas of pedagogy, or 'e-portfolio learning', and IT. Good planning processes and appropriate staff development were also significant factors.